Inequalities in basic activities of daily living among older adults: ELSI-Brazil, 2015 - Andrade, Fabíola Bof de; Duarte, Yeda Aparecida de Oliveira; Souza Junior, Paulo Roberto Borges de; Torres, Juliana Lustosa; Lima-Costa, Maria Fernanda; Andrade, Flavia Cristina Drumond (Revista de Saúde Pública, 2019)
OBJECTIVE: To evaluate the magnitude of wealth-related inequalities in basic activities of daily living among community-dwelling Brazilian older adults and to determine the contribution of demographic, socioeconomic, and health conditions to the inequality. METHODS: We used data from the 2015 Brazilian Longitudinal Study of Aging (ELSI-Brazil) with a nationally representative sample of adults aged 50 years or older. We assessed wealthrelated inequalities in basic activities of daily living by the concentration index. Concentration index was decomposed to determine the contribution of demographic, health, and socioeconomic factors to wealth-related inequalities in basic activities of daily living. RESULTS: The prevalence of disability in the sample was 15.7% (95%CI 14.9–17.6). The concentration index was -0.145 (95%CI -0.194– -0.097), which indicates that disability is concentrated in the poorest individuals in Brazil. Inequalities in basic activities of daily living disability are primarily explained by socioeconomic status (wealth and own education) not by demographic or health factors. CONCLUSIONS: There are avoidable wealth-related inequities for those with a disability in Brazil. The strong contribution of the socioeconomic status highlights the need for new public health policies that promote equity, universality, and integrality, in addition to the expansion of home nursing public services.